1993
DOI: 10.2337/diacare.16.12.1543
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure, Insulin, and C-Peplide Levels in San Luis Valley, Colorado

Abstract: Higher fasting insulin and C-peptide levels are associated with higher blood pressure, but these relationships are modified by sex and degree of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Hyperinsulinemia and insulin resistance are associated with HTN [22][23][24][25]. Thus, incident HTN and serum ferritin level may be mediated by insulin resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Hyperinsulinemia and insulin resistance are associated with HTN [22][23][24][25]. Thus, incident HTN and serum ferritin level may be mediated by insulin resistance.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is consistent with the findings of some other investigators of other countries. [7][8][9][10]12 Elevated insulin level may alter blood pressure as it has effects on the sympathetic nervous system and renal sodium reabsorption. It has been suggested that sympathetic over activity may lead to structural changes in the microvasculature, which ultimately increases blood pressure and decreases peripheral glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The precise nature of the relationship between FSI level and essential hypertension remains still obscure. Therefore, this study has been designed to assess the insulin resistance in adult male with essential hypertension.…”
Section: -10mentioning
confidence: 99%
“…1,10,12,20,36,37 Insulin has been found to cause arteriosclerotic lesions and a proliferation of vascular smooth muscle cells and to promote renal tubular sodium and water absorption which may contribute to the development of cardiovascular disease. 1,10,37,38 Insulin resistance results in an increased hepatic glucose release, and a decreased catabolism of triglycerides contributing to an impaired glucose tolerance and to reduced HDL-cholesterol levels. 1,10 The metabolic complications of android obesity may be mediated by the more pronounced hyperinsulinaemia.…”
Section: Discussionmentioning
confidence: 99%